Gender differences in factors influencing intention to undergo cardiovascular disease health checks: a cross-sectional survey - Cheong, Ai Theng; Seng, Fah Tong; Chinna, Karuthan; Ee, Ming Khoo; Su, May Liew (Public Library of Science, 2020)
Background: Undergo a health check for cardiovascular disease (CVD) is an important strategy to improve cardiovascular (CV) health. Men are reported to be less likely to undergo cardiovascular disease (CVD) health check than women. Gender difference could be one of the factors influencing health seeking behaviour of men and women. We aimed to identify gender differences in factors influencing the intention to undergo CVD health checks. Methods: This was a cross-sectional survey using mall intercept interviews. Malaysians aged ≥30 years without known CVD were recruited. They were asked for their intention to undergo CVD health checks and associated factors. The factors included seven internal factors that were related to individuals’ attitude, perception and preparedness for CVD health checks and two external factors that were related to external resources. Hierarchical ordinal regression analysis was used to evaluate the importance of the factors on intention to undergo CVD health checks, for men and women separately. Results: 397 participants were recruited, 60% were women. For men, internal factors explained 31.6% of the variances in likeliness and 9.6% of the timeline to undergo CVD health checks, with 1.2% and 1.8% added respectively when external factors were sequentially included. For women, internal factors explained 18.9% and 22.1% of the variances, with 3.1% and 4.2% added with inclusion of the external factors. In men, perceived drawbacks of health checks was a significant negative factor associated with likeliness to undergo CVD health checks (coefficient = -1.093; 95%CI:-1.592 to -0.594), and timeline for checks (coefficient = -0.533; 95%CI:-0.975 to -0.091). In women, readiness to handle outcomes following health checks was significantly associated with likeliness to undergo the checks (coefficient = 0.575; 95%CI: 0.063 to 1.087), and timeline for checks (coefficient = 0.645; 95%CI: 0.162 to 1.128). Both external factors 1) influence by significant others (coefficient = 0.406; 95%CI: 0.013 to 0.800) and 2) external barriers (coefficient = -0.440; 95%CI:-0.869 to -0.011) were also significantly associated with likeliness to undergo CVD health checks in women. Conclusions: Both men and women were influenced by internal factors in their intention to undergo CVD health checks, and women were also influenced by external factors. Interventions to encourage CVD health checks need to focus on internal factors and be gender sensitive.